2014
DOI: 10.1080/00207160.2014.985664
|View full text |Cite
|
Sign up to set email alerts
|

An empirical investigation into the effects of chaos on different types of evolutionary crossover operators for efficient global search in complicated landscapes

Abstract: In this study, a comprehensive empirical test is conducted to analyze the effects of two well-known chaotic maps, namely sinusoidal and logistic maps, on the efficacy of double Pareto crossover (DPX), Laplace crossover (LX) and simulated binary crossover (SBX) operators for the global optimization of continuous problems. To do so, 13 well-known numerical benchmark problems in three distinctive dimensions, namely 50D, 100D and 200D, are considered and the genetic algorithm (GA) with simple version and chaos enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 26 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…Indeed, this is a mutation applied to the cloned antibodies previously revised through the recombination. Here, the authors selected the arithmetic graphical search mutation [18] to evolve the antibodies of population CC.…”
Section: Optimum Soc Trajectory Generationmentioning
confidence: 99%
“…Indeed, this is a mutation applied to the cloned antibodies previously revised through the recombination. Here, the authors selected the arithmetic graphical search mutation [18] to evolve the antibodies of population CC.…”
Section: Optimum Soc Trajectory Generationmentioning
confidence: 99%
“…Experimental results demonstrated that the LX-GA outperformed other types of GAs. Consequently, in many studies related to GAs, researchers tend to utilize the LX for performing crossover operations [28,29]. The LX is suitable for optimization problems involving continuous parameters and generates random numbers based on the Laplace distribution, exhibiting good randomness and perturbation properties.…”
Section: Introductionmentioning
confidence: 99%